Relationship Between Body Mass Index With The Incidence Of Anemia In Adolescent Girls - Pasalina, Putri; Ririn Selvia; Erin Desweni; Hendri Devita (International Health Sciences Journal, 2026)
Anemia is a condition in which the hemoglobin level in the blood is less than 12 g/dl. Anemia in adolescents will result in decreased concentration, decreased physical fitness, and growth disorders, so that height and weight do not reach normal levels. The purpose of this study was to determine the relationship between Body Mass Index (BMI) with the incidence of anemia in adolescent girls. This study employed a quantitative analytical method with a cross-sectional approach. It was conducted at SMAN 12 Padang from January to July 2025 with a sample size of 54 female adolescents, using proportional random sampling. The research instruments used were digital scales, microtoise, and digital hemoglobinometer, which were analyzed using the Chi-square test. The results of the study showed that a low BMI was more prevalent in the anemia group (57.4%) than in the non-anemia group (42.6%). The statistical test results showed a significant relationship between BMI with the incidence of anemia in adolescent girls (p-Value (p = 0.000)). Conclusion: There is a significant association between BMI with the occurrence of anemia in adolescent girls. It is hoped that adolescents will gain a better understanding of anemia and nutritional status.